Anarchival Images: The Labour of Chronic Collage - Thain, Alanna (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2019)
This essay develops the concept of “chronic collage” through an analysis of two recent works of media reperformance: Tanya Tagaq’s Nanook of the North (2012–) and Guy Maddin and Galen and Evan Johnson’s The Green Fog (2017). Both are remixes commissioned as live performances by film festivals. Tagaq created a resurgent and resistant new soundtrack to Robert Flaherty’s 1922 ethnographic film Nanook of the North and Maddin sampled media works shot in San Francisco to assemble a remake of Alfred Hitchcock’s Vertigo (1958), with a live soundtrack by Kronos Quartet. Taking an ecosophical approach, this essay describes chronic collage as an anti-extractivist critical technique that plays on lived archives of moving image memory across sites of expropriation, exclusion, and contested history. A dynamic form, chronic collage names the attempt to animate the affective agency of temporal objects.